2017
DOI: 10.1111/1750-3841.13710
|View full text |Cite
|
Sign up to set email alerts
|

Solution Blow Spinning of Food‐Grade Gelatin Nanofibers

Abstract: The primary advantage of nanofibers over larger diameter fibers is the larger surface area to volume ratio. This study evaluated solution blow spinning (SBS) processing conditions for obtaining food-grade gelatin nanofibers from mammalian and fishery byproducts, such as pork skin gelatins (PGs) and high molecular weight fish skin gelatin (HMWFG). HMWFG had a highest intact collagen structure compared to PGs. PGs with different Bloom values, solution viscosities, and surface tensions were compared with HMWFG fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…These suggested that the behavior of FFEs was dominated by the lecithin and the air–water interface might be saturated with lecithin molecules because it was the most surface‐active component in FFE. Although these decreases in surface tension would favor the formation of thinner and uniform nanofibers, those rheological properties related to the chain entanglement should also be considered (Liu et al., , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These suggested that the behavior of FFEs was dominated by the lecithin and the air–water interface might be saturated with lecithin molecules because it was the most surface‐active component in FFE. Although these decreases in surface tension would favor the formation of thinner and uniform nanofibers, those rheological properties related to the chain entanglement should also be considered (Liu et al., , ).…”
Section: Resultsmentioning
confidence: 99%
“…Nanofibers were prepared by solution blow‐spinning (SBS) at 18 °C and 48% relative humidity (RH) according to our previous study (Liu et al., ), with minor modifications. The SBS apparatus consisted of a syringe pump (KD Scientific, Holliston, Mass., U.S.A.), a concentric nozzle, and a source of compressed air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofibers were prepared with the solution blow spinning (SBS) method at 18 °C and 48% relative humidity (RH) according to our previous study [ 26 ], with minor modifications. The SBS apparatus consisted of a syringe pump (KD Scientific, Holliston, MA, USA), a concentric nozzle, and a source of compressed air.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, environmentally-friendly polymers are preferable to traditional petroleum-based polymers for use as the polymeric matrix in food applications [ 1 ]. According to Liu, et al [ 26 ], blow spun nanofibers can be successfully prepared from fish skin gelatin (FSG) using an acetic acid solution as the solvent.…”
Section: Introductionmentioning
confidence: 99%